PERILAKU PETUGAS MEDIS DALAM MERUJUK PASIEN ANTENATAL CARE (ANC) KE RUMAH SAKIT - Hardina, Siti; Idris, Haerawati (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2022)
High referrals can increase hospital workloads and result in increased claims costs to BPJS Health. The purpose of this study was to determine the behavior of health center staff in referring antenatal care patients to hospitals. The research method uses a descriptive qualitative design with a health belief model approach. Informants were selected using a purposive technique. Data were collected using an in-depth interview guide, observation, and document review in one of the primary health care in Palembang City. Data validation is done using the triangulation of sources, methods, and data. This study uses content analysis as a data analysis technique. The results showed that medical staff referred to antenatal care patients when there were indications of illness and high-risk patients. The hospital is chosen based on the consideration of the distance between the patient's house and the hospital. High reference can cause a decrease in capitation. The obstacles in referring to antenatal care patients are more from external obstacles in the form of technical obstacles. Medical staff have confidence and know the limits in referring patients. Medical personnel conduct an examination and confirm the patient's condition before making a referral. The existence of a high referral is due to a request for a referral from a patient. BPJS Health is expected to coordinate with the health center to overcome the referral problem.